Assessing global and gene specific DNA methylation in anorexia nervosa: A pilot study. Issue 2 (2nd October 2013) - Saffrey, Richard; Novakovic, Boris; Wade, Tracey D.
ABSTRACT Objective At present there are no genome‐wide methylation data available in anorexia nervosa (AN) and no studies have examined the potential dynamic nature of DNA methylation during treatment, so it is unclear whether epigenetic disruption established over long periods of malnourishment is reversible. The current study examined global levels of DNA methylation and methylation at a labile imprinted locus in women with AN. Method Buccal swabs were collected from 10 women who were admitted to hospital for treatment of AN and 10 age‐matched healthy controls DNA methylation of LINE‐1 repetitive elements and the H19 imprinting control region was measured using previously validated assays using the Sequenom Mass Array platform. Results No evidence for altered global or gene‐specific DNA methylation was observed in association with AN. Discussion Larger, genome‐wide studies of epigenetic modifications, encompassing both DNA methylation and other epigenetic marks, are required to determine the degree to which AN is associated with specific epigenetic changes, potentially modifiable through appropriate treatments that improve nutrition. © 2013 Wiley Periodicals, Inc. (Int J Eat Disord 2014; 47:206‐210)